The Development of the ICD-11 Classification of Personality Disorders: An Amalgam of Science, Pragmatism, and Politics - Tyrer, Peter; Mulder, Roger; Kim, Youl-Ri; Crawford, Mike J (Annual review of clinical psychology, 2019)
The nomenclature of personality disorders in the 11th revision of the represents the most radical change in the classification history of personality disorders. A dimensional structure now replaces categorical description. It was argued by the Working Group that only a dimensional system was consistent with the empirical evidence and, in the spirit of clinical utility, the new system is based on two steps. The first step is to assign one of five levels of severity, and the second step is to assign up to five prominent domain traits. There was resistance to this structure from those who feel that categorical diagnosis, particularly of borderline personality disorder, should be retained. After lengthy discussion, described in detail here, there is now an option for a borderline pattern descriptor to be selected as a diagnostic option after severity has been determined.